How to minimize the impact caused by global pandemic in Malaysia - Kabir, Sardar Md Humayun; Haque, A. K. M. Ahasanul; Rahman, Mohammad Moshiur; Abd, Zainatul Shuhaida (RMP Publications, 2020)
Infectious diseases like influenza, malaria are proved to be hazardous for humankind. While some became epidemic to a few geographical regions, the new Coronavirus (Covid-19) outbreak in almost every regions of the world made it a pandemic. Although clinical research and development evolved in today’s modern age, a successful and recognized treatment over the disease has not been found yet. The global pandemic is probing countless impact on public health, the global economy, social and religious wellbeing. Previous researchers have undoubtedly emphasized the necessity and utter significance of pandemic preparedness at the global level. Still, very few have focused on the impacts of a global pandemic in Malaysia. The suggestions from the findings of this study will contribute to developing new knowledge in the functional domains of contingency during a pandemic crisis. The results will also help in developing governmental policy decisions for public health, economic development, social welfare and religious actions. Stringent measures during pandemic preparedness are discussed at the end of this paper.